Macroevolution - Saupe, E; Myers, C (Springer, Cham, 2020)
Macroevolution is the study of patterns and processes associated with evolutionary change at and above the species level, and includes investigations of both evolutionary tempo and mode. Tempo refers to the rate or pace of change, whereas mode refers to how that change occurs. Both the tempo and mode of macroevolution are difficult to predict based solely on the study of populations, organisms, and genes – the realm of microevolution. Important macroevolutionary discoveries include the observation that species rarely accrue net morphological change over their lifespans of millions of years, that episodes of mass extinction substantially modify the evolutionary trajectory of life on Earth, and that variation in rates of speciation, extinction, and morphological change occurs over time, in different habitats, and across groups. The potential disconnect between microevolution and macroevolution suggests different processes may operate at different levels of biological organization, and at different spatial and temporal scales. Thus, macroevolution should be considered in concert with microevolution when determining the processes that have shaped the coevolution of Earth and life.